Pengaruh Kualitas Pelayanan Akademik dan Costumer Relationship Management Terhadap Kepuasan Mahasiswa Reguler Pagi USB YPKP Bandung - Anissa Primafidyanti; Sumeidi Kadarisman (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2019)
This research aims to detremine, describe and analyze the effects of academic service and customer relationship management on student satisfaction. The method used is decriptive verificative with quantitative approach. Sample taking used cluster proportionare random sampling of 92 people. Data analysis showed that r2 value is 0,486. Based on the test results the partial hypotesis for the quality of thitung academic service, the value of thitung is 3,410 while ttabel’s value is 1,986 which means that the quality of academic service has a significant impact on student satisfaction. thitung value for customer relationship management is 3,509 while ttabel’s value is 1,986 which means that customer relationship management has a significant impact on student satisfaction. Based on simultaneously hypotesis Fhitung’s value is 42,129 while Ftabel’s value is 1,986 which means that simultaneously there is a significant effect between the quality of academic service and customer relationship management approach to student satisfaction.